Exploring Inpatients' Experiences of Healing and Healing Spaces - Lorissa MacAllister PhD, AIA; Dawn Bellanti MSN, CRNP; Bonnie R. Sakallaris PhD, RN (Journal of Patient Experience, 2016)
In order to understand a patient’s healing experience it is essential to understand the elements that they, the patient, believes contributed to their healing. Previous research has focused on symptom reducers or contributors through environment such as stress. A person’s experience of healing happens over time not instantaneous. Therefore, in this study, the interviews with patients happened after forty-eight hours of hospitalization. This mixed methods study describes the experiences of seventeen inpatients from two healthcare systems using a phenomenological approach combined with evidence based design evaluation methods to document the setting. The qualitative data was analyzed first for reoccurring themes then further explored and defined through quantitative environmental observations. The seventeen patients defined healing as “getting better/well.” Seventy three statements were recorded about contributors and detractors to healing in the physical environment. Three primary themes emerged from the data as positive influencers of a healing experience: being cared for, being comfortable and experiencing something familiar or like home. These results demonstrate that patients perceive their inpatient healing experience through a supported environment.